Application of Rating Scale Method to Design and Construct an Employee Performance Assessment Application System in National Charity Institutions - Annisa Wahdiniawati, Siti; Zulkifli; Chrisnawati, Giatika; Sili Antari, Ni Luh; Mustika, I Ketut (Jurnal Informasi dan Teknologi, 2024)
This research aims to find out how to design and build an employee performance assessment information system using the rating scale method. The data collection methods used were observation, interviews, and literature study. The research used the rating scale as the employee performance assessment method. The author used the Rapid Application Development (RAD) method in system development. The researcher designed an employee performance assessment information system using UML (Unified Modeling Language) tools at this stage. In this stage, the system is built using the PHP and MySQL programming languages for the database. The research results show that the developed performance appraisal system can provide significant benefits in monitoring employee performance more efficiently. Using this system makes the performance appraisal process easier, reduces file buildup, and increases the speed of the process from one week to only three days to complete the appraisal report. A data collection center also provides additional value by ensuring the security and orderliness of information.